बस्तर के गोंड़ जनजाति की धार्मिक अवधारणा - Kiran Nuruti (Gondwana- Gondi Sahitya Parishad Nagpur, 2012)
The book describes about the culture and religion of the Gond tribe.
Bastar Ke Gond Janjati Ki Dharmik Avadharana
Keywords: Gondi; बस्तर के गोंड़ जनजाति की धार्मिक अवधारणा; Bastar Ke Gond Janjati Ki Dharmik Avadharana; Culture and Religion; Gondi; Hindi